The modeling of a tokamak plasma discharge, from first principles to a flight simulator. (1st April 2022) - Fable, E; Janky, F; Treutterer, W; Englberger, M; Schramm, R; Muraca, M; Angioni, C; Kudlacek, O; Poli, E; Reich, M; Siccinio, M; Tardini, G; et al.
Abstract: A newly developed tool to simulate a tokamak full discharge is presented. The tokamak 'flight simulator' Fenix couples the tokamak control system with a fast and reduced plasma model, which is realistic enough to take into account several of the plasma non-linearities. A distinguishing feature of this modeling tool is that it only requires the pulse schedule (PS) as input to the simulator. The output is a virtual realization of the full discharge, whose time traces can then be used to judge if the PS satisfies control/physics goals or needs to be revised. This tool is envisioned for routine use in the control room before each pulse is performed, but can also be used off-line to correct PS in advance, or to develop and validate reduced models, control schemes for future machines like a commercial reactor, simulating realistic actuators and sensors behavior.